PENERAPAN KONSEP EDUWISATA PADA PROGRAM KAMPUNG IKLIM (PROKLIM) - Maulida, Siti Zakiyah; Pritamie, Nola; Taqiuddin, Said Ashari; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
Climate change is currently increasingly felt, including in Indonesia. Indonesia is very vulnerable to the effects of global warming and climate change due to its geographical situation, one of the efforts is through the Climate Village Program (PROKLIM). The aim is to determine the application of the concept of eduwisata in the proklim program in Palasari Hamlet, Sukahurip Village in strengthening community resilience to climate change and reducing greenhouse gas emissions. Using the data sampling technique method is done by means of primary data and secondary data. Palasari Hamlet has natural wealth, culinary and handicrafts that can be used as tourist destinations so that we develop an educational tourism program through tour packages that will be aimed at the wider community. The result of our service is to hold an edu-tourism program with the concept planned to be a tour package program in Palasari Hamlet. The tour package that we designed contains activities from one place to another while learning. The program that we do at Proklim is expected to be able to become a forum for community education to become agents of change in the environment where they live and can improve the quality of life of the community in the area around the implementation of the program.